The slow end of the ICE age in Germanysinsights from job postings on the automotive industry's trajectory - Thomas Fackler; Oliver Falck; Moritz Goldbeck; Fabian Hans; Annina T. Hering (EconPol Forum, 2024)
The debate on phasing out internal combustion engines (ICE) has resurfaced in Germany amid an economic downturn; whether this is smart appears questionable. To monitor in real time where the industry is headed, analyzing job postings provides reliable insights into the ongoing strategic shifts in the automotive sector. From mid-2019, postings of EV-focused firms have consistently exceeded those of ICE-focused firms, eventually being about twice as high by the end of 2023. However, this gap in postings between EV- and ICEfocused firms has shrunk by 60 percent since December 2023, indicating a slowdown of the transition to e-mobility. EV-focused firms scale back job ads for production-related roles disproportionately while ICE-focused firms decrease hiring to a greater extent for transformation-related occupations.
Keywords: 330